Simplify (9x ^ 2 - 6x + 2) - (x ^ 2 + 4x - 39) (1 point)

The difference of the polynomials is __

1 answer

To simplify the expression \((9x^2 - 6x + 2) - (x^2 + 4x - 39)\), we will first distribute the negative sign across the second polynomial, and then combine like terms.

Start by rewriting the expression:

\[ 9x^2 - 6x + 2 - (x^2 + 4x - 39) \]

Distributing the negative sign gives us:

\[ 9x^2 - 6x + 2 - x^2 - 4x + 39 \]

Now, combine like terms:

  1. For the \(x^2\) terms: \(9x^2 - x^2 = 8x^2\)
  2. For the \(x\) terms: \(-6x - 4x = -10x\)
  3. For the constant terms: \(2 + 39 = 41\)

Putting it all together, we have:

\[ 8x^2 - 10x + 41 \]

Thus, the difference of the polynomials is

\(\boxed{8x^2 - 10x + 41}\).

Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions